2021
DOI: 10.1016/j.isci.2021.102780
|View full text |Cite
|
Sign up to set email alerts
|

Anemia during SARS-CoV-2 infection is associated with rehospitalization after viral clearance

Abstract: Patients rehospitalized after SARS-CoV-2 clearance have distinct laboratory test profiles Rehospitalized patients have lower hemoglobin before and during SARS-CoV-2 infection Rehospitalized patients are more likely to experience anemia during active infection

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Another report identified an anemia 1 year prior and during acute illness being strongly associated with post-clearance rehospitalization independent of the intensive care unit admission status or other covariates. Similar finding was with AKI as well [24]. Chronic COVID-19 syndrome, also known as post-COVID-19 or long-COVID-19, developed 23 patients (58%) that is consistent with previous reports [25].…”
Section: Discussionsupporting
confidence: 90%
“…Another report identified an anemia 1 year prior and during acute illness being strongly associated with post-clearance rehospitalization independent of the intensive care unit admission status or other covariates. Similar finding was with AKI as well [24]. Chronic COVID-19 syndrome, also known as post-COVID-19 or long-COVID-19, developed 23 patients (58%) that is consistent with previous reports [25].…”
Section: Discussionsupporting
confidence: 90%
“…1 ). Eventually, 36 studies were included in the present systematic review and 28 were incorporated in the meta-analysis [ 7 , 9 , 11 , [13] , [14] , [15] , [16] , 19 , 20 , 23 , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ]. Overall, 28 articles were included in phase 1 to determine risk factors and outcome of readmitted COVID-19 patients, and 19 articles were included in phase 2 to determine the cause of readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown that anemia is an independent risk factor for severity of and length of recovery from COVID-19 [41][42][43][44][45]. Anemia has also been found to be signi cantly associated with COVID-19 mortality.…”
Section: Pre-covid-19 Anemia Effect Modi Cationmentioning
confidence: 99%